2011
DOI: 10.1007/s00432-011-0992-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of pancreatic juice for the identification of biomarkers of pancreatic cancer

Abstract: We have shown that pancreatic juice is a good source of pancreatic cancer tumor markers. Further studies are needed to determine the clinical implications of REG1α and other markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…PRDX6 has been reported to be implicated in the development and progression of several human diseases, such as Alzheimer's disease (137), Parkinson's dementia (138), diabetes (139), cataractogenesis (140) and cancer. Concerning the neoplastic diseases, elevated levels of PRDX6 have been described in breast cancer (141), in malignant mesothelioma (67), in bladder cancer (61), in esophageal cancer (142), in lung (143), ovarian (87) and pancreas (144) cancer, in cancer of the gingivo-buccal area (145), and in lymphoma (146). Elevated expression levels of PRDX6 have been associated with a more invasive phenotype and metastatic potential of breast cancer (147), and with a worse prognosis of clinically localized prostate cancer following radical prostatectomy (148).…”
Section: Prdxs In Tumorigenesismentioning
confidence: 99%
“…PRDX6 has been reported to be implicated in the development and progression of several human diseases, such as Alzheimer's disease (137), Parkinson's dementia (138), diabetes (139), cataractogenesis (140) and cancer. Concerning the neoplastic diseases, elevated levels of PRDX6 have been described in breast cancer (141), in malignant mesothelioma (67), in bladder cancer (61), in esophageal cancer (142), in lung (143), ovarian (87) and pancreas (144) cancer, in cancer of the gingivo-buccal area (145), and in lymphoma (146). Elevated expression levels of PRDX6 have been associated with a more invasive phenotype and metastatic potential of breast cancer (147), and with a worse prognosis of clinically localized prostate cancer following radical prostatectomy (148).…”
Section: Prdxs In Tumorigenesismentioning
confidence: 99%
“…In this study, 14 proteins were found to be upregulated in the cancerous samples, including MMP-9, DJ-1, and A1BG. A third study was published by Parks et al [23], who used 2-D gel electrophoresis combined with MALDI-TOF-MS, and identified 35 proteins, including BIG2, PRDX6, and REG1a, that were upregulated by at least two-fold in pancreatic cancer patients compared to normal control and chronic pancreatitis controls. These studies clearly demonstrate the feasibility of using serum, urine, and pancreatic juice to identify biomarkers and potential proteins for a diagnostic panel.…”
Section: Biological Samples For Analysismentioning
confidence: 95%
“…Due to proximity to the pancreas, pancreatic juice can also represent a rich source of biomarkers for pancreatic cancer [23][24][25]. However, since endoscopic retrograde cholangiopancreatography, the process from which pancreatic juice is obtained, is a complex process that carries a risk of development of pancreatitis, proteomic analysis of pancreatic juice from nondiseased humans for use as comparisons to pancreatic cancer patient samples has been limited [26].…”
Section: Biological Samples For Analysismentioning
confidence: 99%
“…When the proteome of pancreatic juice was investigated, again using 2D gel electrophoresis and MALDI-TOF MS/MS, MMP9, DJ1 and A1BG were elevated in cancer compared with control, suggesting that these may be helpful in differentiating between pancreatic ductal carcinoma and chronic pancreatitis (Tian et al 2008). However, a similar study (Park et al 2011) that compared the pancreatic juice following secretin stimulation in patients with pancreatic cancer, chronic pancreatitis and no disease found that BIG2, PRDX6 and REG1a were over-expressed in cancer and confirmed this with immunohistochemical analysis of cancer tissue. This highlights the potential variability between similar studies and, given the way in which proteins are identified, the potential inaccuracy in reporting.…”
Section: Mass Spectrometry and Pancreatic Tumoursmentioning
confidence: 96%